ETHNOCULTURE OF THE NOGAIS AND THE HERITAGE OF DASHT-I-KIPCHAK (Journal of Philosophy Culture and Political Science, 2022)
In the modern world, in which significant changes are taking place, the processes of globalisation and unification of cultures are becoming increasingly important. In this regard, the issue of searching for ways of spiritual renewal and reassessing the priorities of further cultural development of Turkic peoples, the preservation of the fundamental spiritual values of Turkic ethnoculture, unique and original, is of particular importance. Turkic-speaking thinkers have always strived to build a holistic philosophical image of man. The philosophical approach to the human being implies revelation of its essence, concrete and historical determination of the forms of its activity, the disclosure of various historically existing forms of its being. The anthropocentric philosophy of the Eurasian thinkers of the Middle Ages reveals man's place in the world and his relation to the world, analyses the question of who man can become, realising his potential, what is the ratio of the sacred and profane in him, who is the «perfect man».Key words: The Turkic culture of Nogay, Dagestan, Desht-i-Kipchak, nomadism, the Middle Ages, the Great Silk Road.